Viral Marketing, Brand Awareness, dan Lifestyle: Dampaknya Terhadap Keputusan Pembelian Melalui Minat Beli - Widiyanti, Aprillia Putri; Sukarno, Aji; Rosyada, Fani Yulia; Koranti, Komsi; Artanti, Anisrina (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the influence of viral marketing, brand awareness, and lifestyle on purchasing decisions with the mediation variable of purchase interest at Point Coffee Indomaret. This study uses primary data collected through the distribution of questionnaires from 250 respondents who are consumers of Point Coffee Indomaret, using purposive sampling. Data were analyzed using partial least square-structural equality modeling (PLS-SEM) with the help of the SmartPLS statistical application. The results of the study indicate that viral marketing, brand awareness, and lifestyle have an effect on purchase interest. Viral marketing, lifestyle, and purchase interest have an effect on purchasing decisions. Viral marketing has an effect on purchasing decisions with purchase interest as a mediation variable, brand awareness has no effect on purchasing decisions with purchase interest as a mediation variable, lifestyle has an effect on purchasing decisions with purchase interest as a mediation variable.